Pengaruh Lama Fermentasi Dedak Gandum Terhadap Kandungan Serat Kasar, NDF dan ADF - Mesang, Sarintan Novite I.; Oematan, Gustaf; Mullik, Marthen L.; Dami Dato, Twen O (Animal Agricultura, 2024)
This study aims to determine the effect of the duration of wheat bran fermentation on the content of crude fiber, neutral detergent fiber (NDF), and acid detergent fiber (ADF). The design used was the Completely Randomized Design (CRD) method with 4 treatments and 4 replications, resulting in 16 experimental units. The treatments consisted of fermentation durations of 0 days (LF0), 2 days (LF2), 4 days (LF4), and 6 days (LF6). Prior to fermentation, wheat bran was mixed with an inoculum solution at a 1:1 ratio. The inoculum was made from a mixture of 16 liters of clean water, 30 ml of EM4, 100 ml of liquid sugar, and 100 ml of fresh cow feces liquid taken from cows fed with lamtoro and fresh grass. The variables studied in this research were the content of crude fiber, neutral detergent fiber (NDF), and acid detergent fiber (ADF). The data were analyzed using analysis of variance (ANOVA) for CRD where the alpha value was set at 0.5%, and differences between treatments were followed by Duncan's test using SPSS version 25. The results of the statistical analysis showed that the duration of wheat bran fermentation had a very significant effect (P<0.01) in reducing all fiber variables. The total value of crude fiber content decreased from 51.95% (LF0) to 42.86% (LF6), likewise NDF decreased from 36.55% (LF0) to 29.90% (LF6), and ADF content decreased from 13.62% (LF0) to 9.12% (LF6). Based on the results of this study, it can be concluded that the longer fermentation of wheat bran using fresh cow feces liquid as an inoculum is capable of reducing the content of crude fiber, NDF, and ADF with a fermentation duration of 6 days (LF6), obtaining total values of crude fiber content (42.86%), NDF (29.90%), and ADF (9.12%).